Understanding of anti-cancer properties of Neolamarckia cadamba (Kalempayan) leaves extract on breast cancer cell - Razali, Shakirah; Hassan, Habibah; Firus Khan, Al'aina Yuhainis; K Jalal, Tara; Abdul Jamil, Muhammad Mahadi; Johan, Muhammad Farid; Mohammad, Mardhiah; Draman, Samsul; Salleh, Azir; Khatib, Alfi; Hashim, Ridzwan; Abdul Wahab, Ridhwan (2016)
Natural products have been used in treating illnesses since ancient times. Neolamarckia cadamba (N. cadamba) plant, locally known as Kalempayan, is an Ayurvedic medicine. It has been used by Indian folklore for treatment such as fever, anaemia, stomatitis, and infectious diseases. This Rubiaceae family plant indicates that it has a therapeutic potential against diseases, including cancer. Therefore, this study aimed to investigate the chemopreventive effect of N. cadamba’s leaves extract (NCE) with regard to the induction of apoptosis and cell cycle arrest against human breast adenocarcinoma cancer cell-line (MCF-7). MCF-7 cells were seeded at 4.7 x 104 cells/well in 6-well plates. The cells were treated with series concentration of NCE. The 50% inhibitory concentration (IC50) of NCE and its antiproliferative effect were measured using Trypan blue exclusion method was determined as 0.125 mg/ml. The flow cytometric analysis was performed in MCF-7 revealed the NCE inhibited the cell proliferation through induction of apoptosis and cell cycle arrest. The present study demonstrates that the NCE has a positive potential as a chemopreventive agent. Further research need to be done to identify the molecular mechanism related to induction of apoptosis and cell cycle arrest in breast cancer cells.